Urban development around bus rapid transit stops in seven cities in Latin-America (2018)
Although bus rapid transit (BRT) has become a popular transportation innovation worldwide, little is known about the built environment around the stops of these systems. A typology of urban development around 81 BRT stops in 7 cities in Latin America was developed and their daily BRT ridership examined. Primary and secondary data collected around the stops were the basis for factor and cluster analyses. Ten stop types were identified, with some types including attributes consistent with expectations of transit-oriented development areas. Other stops captured conditions prevalent in many cities in Latin America: mixed land uses, informal housing distant from activity nodes, large commercial developments, and a relative absence of green spaces open to the public. Confirming expectations, stop types with a higher transit orientation were more likely to have higher ridership than other stops such as those burdened by incompatible land uses and barriers to station access. © 2017 Informa UK Limited, trading as Taylor and Francis Group.